2013
DOI: 10.1136/bjophthalmol-2013-303386
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoebakeratitis: study of the 5-year incidence in Israel: Table 1

Abstract: AK is mostly attributable to the use of contact lenses. As contact lenses are popular in Israel, we expected a higher incidence rate. A lower than expected incidence rate may indicate insufficient awareness of AK in Israel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…This difference with the culture method could be explained as the culture of specimens is a highly specific diagnostic method, but also limited by high false-negative rates. Studies in the United States and United Kingdom concerning culture methods reported sensitivity values from 50 to 57% [ 44 ]. Moreover, large-volume specimens such as observed in contact lens solutions have a demonstrable dilutional effect and are therefore subject to poor smear and culture results.…”
Section: Discussionmentioning
confidence: 99%
“…This difference with the culture method could be explained as the culture of specimens is a highly specific diagnostic method, but also limited by high false-negative rates. Studies in the United States and United Kingdom concerning culture methods reported sensitivity values from 50 to 57% [ 44 ]. Moreover, large-volume specimens such as observed in contact lens solutions have a demonstrable dilutional effect and are therefore subject to poor smear and culture results.…”
Section: Discussionmentioning
confidence: 99%
“…In a case of threatening or completed perforation of the cornea, the surgery must be performed urgently. Some authors recommend systemic steroids prior to surgery if concomitant limbitis or scleritis is present [69].…”
Section: Treatment Recommended In Management In Akmentioning
confidence: 99%
“…The size of corneal graft should be minimum to excise an inflamed and necrotic tissue. Although remaining clinically healthy cornea is frequently also infected, this tissue should be saved because of the higher risk of rejection with large/decentrated grafts and because the possibility of repeat grafting should be kept in mind in the event of recurrence; a further graft represents a new food source for the organism and can be used to attract residual amoebae [69].…”
Section: Treatment Recommended In Management In Akmentioning
confidence: 99%
“…The infections caused by Acanthamoeba include Acanthamoeba keratitis (AK) among healthy individuals, especially those wearing contact lenses, and a life threatening Granulomatous amoebic encephalitis (GAE) infection of the central nervous system (CNS) among immunocompromised population [5,6]. Although the incidence of AK/GAE is different around the world (0.13-33 cases per million), the rates have been steadily increasing throughout recent years, especially in developed countries [7][8][9][10][11][12][13]. Since GAE is found in immunocompromised individuals, the mortality rate is quite high ranging from 95 to 98% among infected patients [14,15].…”
Section: Introductionmentioning
confidence: 99%